Myocardin regulates mitochondrial calcium homeostasis and prevents permeability transition. Issue 10 (November 2018) - Mughal, Wajihah; Martens, Matthew; Field, Jared; Chapman, Donald; Huang, Jianhe; Rattan, Sunil; Hai, Yan; Cheung, Kyle; Kereliuk, Stephanie; West, Adrian; Cole, Laura; Hatch, Grant; et al.
Abstract Myocardin is a transcriptional co-activator required for cardiovascular development, but also promotes cardiomyocyte survival through an unclear molecular mechanism. Mitochondrial permeability transition is implicated in necrosis, while pore closure is required for mitochondrial maturation during cardiac development. We show that loss of myocardin function leads to subendocardial necrosis at E9.5, concurrent with elevated expression of the death gene Nix. Mechanistically, we demonstrate that myocardin knockdown reduces microRNA-133a levels to allow Nix accumulation, leading to mitochondrial permeability transition, reduced mitochondrial respiration, and necrosis. Myocardin knockdown elicits calcium release from the endo/sarcoplasmic reticulum with mitochondrial calcium accumulation, while restoration of microRNA-133a function, or knockdown of Nix rescues calcium perturbations. We observed reduced myocardin and elevated Nix expression within the infarct border-zone following coronary ligation. These findings identify a myocardin-regulated pathway that maintains calcium homeostasis and mitochondrial function during development, and is attenuated during ischemic heart disease. Given the diverse role of Nix and microRNA-133a, these findings may have broader implications to metabolic disease and cancer.